Legal Protection for Cyberbullying Victims Through Social Engineering in Cybercrime - Rizky Wijayanto; Ahmad Ma’mun Fikri; Yan Nurcahya; Arba'iyah Mohd Noor (RechtIdee, 2025)
The development of information and communication technology has created a new space for interaction through digital media, bringing not only benefits but also various forms of cybercrime, one of which is cyberbullying. This phenomenon is increasingly complex when carried out through social engineering techniques, namely the psychological manipulation of victims to obtain information, instill fear, or pressure them mentally and socially. Social engineering-based cyberbullying not only impacts the victim's psychological aspects but also causes social, reputational, and even economic losses. This article aims to analyze the forms of cyberbullying that use social engineering and examine the legal protections available to victims within the cyber law framework in Indonesia. The research method used is normative legal research with a statutory and conceptual approach, which examines related regulations, such as the Electronic Information and Transactions Law, the Criminal Code, and other relevant regulations. The results of the study indicate that although positive legal instruments have provided a basis for protection for victims of cyberbullying, regulations related to social engineering are still implicit and have not been specifically regulated. Therefore, it is necessary to strengthen regulations, improve digital literacy, and adopt an integrated preventive and repressive approach to ensure effective legal protection for victims of cyberbullying in the digital era.